POSSIBILITIES OF BREAST FEEDING ORGANIZATION FOR CHILDREN WITH PERINATAL LESIONS OF CENTRAL NERVOUS SYSTEM - O. L. Lukoyanova; T. E. Borovik; G. V. Yatsik; I. A. Belyaeva; V. I. Furtsev (Вопросы современной педиатрии, 2012)
Acute and/or chronic hypoxia is a leading cause of perinatal lesions of central nervous system. Severe consequences of this condition can be the reason of temporary withdrawal from breast-feeding started soon after birth. Study objectives included: scrutiny of lactation establishment, influence of various factors on lactation duration in mothers of children with perinatal lesions of CNS. Study included 86 pairs mother-child, with duration of 12 months. It has been shown that in cases where breast feeding was impossible, regular expression of breast milk with the help of breast pump in the early lactation period allows not only to organize breast feeding by the time of discharge from the hospital, but also to extend its duration almost to the normal one. Severity of perinatal CNS lesion does not correspond with the duration of lactation period of the mother.